Concentration dependent cardiotoxicity of terodiline in patients treated for urinary incontinence. Issue 1 (July 1995) - Thomas, S. H.; Higham, P. D.; Hartigan-Go, K.; Kamali, F.; Wood, P.; Campbell, R. W.; Ford, G. A.
Abstract : OBJECTIVE–Terodiline, an antimuscarinic and calcium antagonist drug, was used to treat detrusor instability but was withdrawn in 1991 after provoking serious ventricular arrhythmias associated with increases in the corrected QT interval (QTc). This research was performed to relate drug induced electrocardiographic changes in asymptomatic recipients to plasma concentrations of the R(+) and S(-) terodiline enantiomers. SETTING–Urological and geriatric clinics and wards. SUBJECTS–Asymptomatic patients taking terodiline in stable dose. METHODS–Electrocardiograms (50 mm/s) were collected from patients while they were taking terodiline and compared with ECGs obtained before or after terodiline. QT interval, heart rate corrected QT interval (QTc), and QT dispersion (QTd) were measured. Drug induced electrocardiographic changes were related to plasma concentrations of R(+) and S(-) terodiline. RESULTS–During terodiline treatment mean QTc and QTd were prolonged (491(43) and 84 (35) ms 1/2) compared with measurements made off therapy (443 (33) and 42 (17) ms 1/2, paired t tests, P < 0.002 and P < 0.01 respectively) in the 12 patients in sinus rhythm. The mean (95% confidence interval) drug induced increases were 48 (23 to 74) ms 1/2 for QTc and 42 (13 to 70) ms 1/2 for QTd. These increases correlated with total plasma terodiline (QTc: r = 0.77, P < 0.006, QTd: r = 0.68, P < 0.025) and with plasma concentrations of both terodiline enantiomers. CONCLUSIONS–Terodiline increases QTc and QTd in a concentration dependent manner. It is not clear whether this is a stereoselective effect and, if so, which enantiomer is responsible. The results suggest that drug induced torsade de pointes is a type A (concentration dependent) adverse drug reaction.